Higher Education and Development in South-East Asia - Unesco; Hunter, Gay (V-3, Pt.-1); Noss, Richard (V-3, Pt.-2); Hayden, Howard , (V-1); International Association of Universities, Paris (France). (Paris : Unesco, 1967)
This document, the first part of the third volume of a study concerned with the role of institutions of higher education in the development of countries in South-East Asia, appraises the high-level manpower needs of the region. The report is divided into two sections: the first includes the major comments on the position of high-level manpower in the whole region, an extremely brief summary of conclusions reached in each country and a set of four comparative tables. The second consists of ten individual studies in much greater detail containing many individual recommendations. Individual studies concern Burma, Thailand, Malaysia, Indonesia, Cambodia, Viet-nam, and the Philippines. Related documents are HE 004 652, HE 004 651, and HE 004 650. (MJM)
Vol. 1, Director;s Report / by Howard Hayden -- V -- 3, part 1, High-level manpower for development / Gay Hunter -- V -- 3, part 2, language policy and higher education / Richard Noss
Sponsoring Agency: Ford Foundation, New York, NY.
Keywords: Comparative Education; Developing Nations; Educational Development; Educational Finance; Educational History; Educational Improvement; Educational Innovation; Foreign Countries; Higher Education; Labor Needs; Labor Utilization; Social Development; Asia (Southeast); Burma -- Cambodia -- Indonesia -- Malaysia -- Philippines -- Thailand -- Viet Nam